2020
DOI: 10.1016/j.gerinurse.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of nurse practitioner (NP)-Provided home visits: A systematic review

Abstract: Background With the shortage of primary care providers to provide home-based care to the growing number of homebound older adults in the U.S. Nurse Practitioners (NPs) are increasingly utilized to meet the growing demand for home-based care and are now the largest type of primary care providers delivering home-visits. Purpose The purpose of this study was to systematically examine the current state of the evidence on health and healthcare utilization outcomes associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Two studies that measured objective health outcomes found a greater decrease in hemoglobin A1c (Stone et al, 2010) or more health risk reduction among intervention participants (Hahn & Aronow, 2005). Palfrey et al (2004) found that providing NP home visits to children with special needs significantly improved school and work attendance for children and parents. Finally, one study found that children with asthma had fewer courses of oral steroids, fewer nighttime symptoms, and better asthma control (Swartz & Meadows-Oliver, 2019).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Two studies that measured objective health outcomes found a greater decrease in hemoglobin A1c (Stone et al, 2010) or more health risk reduction among intervention participants (Hahn & Aronow, 2005). Palfrey et al (2004) found that providing NP home visits to children with special needs significantly improved school and work attendance for children and parents. Finally, one study found that children with asthma had fewer courses of oral steroids, fewer nighttime symptoms, and better asthma control (Swartz & Meadows-Oliver, 2019).…”
Section: Resultsmentioning
confidence: 97%
“…Ten of 12 studies addressing health care utilization found that NP home visits led to fewer hospitalizations ( n = 10) (Bryant & Gaspar, 2014; Dick & Frazier, 2006; Jones, DeCherrie, et al, 2017; Kobb et al, 2003; Muramatsu et al, 2004; Palfrey et al, 2004; Stuck et al, 1995; Swartz & Meadows-Oliver, 2019; Wajnberg et al, 2010). The intervention group in the two studies without significant utilization changes had a trend of decreased hospitalizations (Coppa et al, 2018; Counsell et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations